Effects of Mediterranean agricultural residues on microbial community and anaerobic digestion performance. (24th November 2021) - Valenti, Francesca; Rojas‐Sossa, Juan Pablo; Zhong, Yuan; Porto, Simona M. C.; Toscano, Attilio; Marsh, Terence; Dale, Bruce E.; Liu, Yan; Liao, Wei
Abstract: Understanding the effects of regionally available residues, wastes, and purpose‐grown energy crops on anaerobic microbes and corresponding digestion performance is important for designing and implementing suitable anaerobic digestion systems to manage them appropriately and to use them for bioenergy generation. This study analyzed and compared dynamic changes in anaerobic microbes and digestion performance using mixtures of six different materials (citrus pulp, olive pomace, cattle manure, poultry litter, whey, and corn silage) generated from Mediterranean agro‐industry. The results indicate that the feedstock mixture (FM3) with low citrus pulp (26% dry matter) and high olive pomace (18% dry matter) reached stable methane production of 210 mL methane/g volatile solids ( VS ) loading within 30 days after the start up. In contrast, the feedstock mixture (FM1) with high citrus pulp (44% dry matter) and low olive pomace (0% dry matter) required a longer time of at least 70 days to achieve a good methane production of 209 mL methane/g VS loading. The microbial community analysis and corresponding non‐metric dimensionless scaling (NMDS) analysis revealed dynamic relationships between microbial community, feedstock mixture, and digestion time. The feedstock mixtures with low citrus pulp content (FM2 and FM3) facilitated the accumulation of Archaea (i.e., Methanosarcinaceae ), which led their digestion to reach stable methane production quicker than the digestion of FM1. This study provided useful information to valorize agricultural residues and wastes for bioenergy production in the Mediterranean region. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd